2016
DOI: 10.2196/games.5460
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Engagement and Neurophysiological Measures of Attention in Motion-Controlled Video Games: A Randomized Controlled Trial

Abstract: BackgroundVideo games and virtual environments continue to be the subject of research in health sciences for their capacity to augment practice through user engagement. Creating game mechanics that increase user engagement may have indirect benefits on learning (ie, engaged learners are likely to practice more) and may also have direct benefits on learning (ie, for a fixed amount of practice, engaged learners show superior retention of information or skills).ObjectiveTo manipulate engagement through the aesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…It also referred to characters and situations that had been introduced during task instructions, requiring children to use working memory to make connections with information that had been presented earlier. Leiker et al (2016) linked learner engagement to greater information processing. Given that both groups reported high engagement in the task, and that the task was difficult (as evidenced by the fact that no participant achieved the maximum score), the added narrative may have been an extra cognitive burden that was a detriment to performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also referred to characters and situations that had been introduced during task instructions, requiring children to use working memory to make connections with information that had been presented earlier. Leiker et al (2016) linked learner engagement to greater information processing. Given that both groups reported high engagement in the task, and that the task was difficult (as evidenced by the fact that no participant achieved the maximum score), the added narrative may have been an extra cognitive burden that was a detriment to performance.…”
Section: Discussionmentioning
confidence: 99%
“…were the first to explore engagement-mediated learning effects in humans in an experiment demonstrating that playing a more aesthetically-enriched video game improved skill retention as compared to playing a sterile version of the game. A follow-up study using electroencephalography showed that engaged learners had increased information processing, as measured by reduced attentional reserve (Leiker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not find a significant correlation between engagement, motivation and retention scores. A follow-up study using electroencephalography did not replicate the finding that the more enriched practice condition enhanced learning, it did show that more engaged learners had increased information processing, as measured by reduced attentional reserve [25].…”
Section: Introductionmentioning
confidence: 99%
“…The first descriptions of MK for medical use were in relation to physical and cognitive rehabilitation [37]. Subsequent experiences in this field showed that additional studies were required on issues such as effectiveness, commitment, and usability [38-40]. Its use in an operating room was first reported in 2011, at Sunnybrook Hospital in Toronto, when it was used to view magnetic resonance imaging and computed tomography scans, eventually giving rise to the GestSure system [13].…”
Section: Introductionmentioning
confidence: 99%